Assessment Of Immunization Status of Children Between 12-23 Months in Allahabad District - Arshiya Masood; S Dwivedi; G. Singh; M A Hassan; Arun Singh (Medsci Publications, 2011)
Objectives:  This study was carried out to assess the immunization status of children in the age group 12-23 months and to know the reasons for non-immunization of children Methods: This was a cross-sectional study. We included 228 children (156 in rural and 72 in urban areas) in 12-23 months of age group by stratified cluster sampling design from Rural and Urban areas of Allahabad. Mothers of the children were interviewed using a predesigned schedule. Result and Conclusion: Only around 31 percent of children were found to be fully immunized while around 24 percent were partially and 45 percent were not immunized at all. Vitamin A prophylaxis showed a decline from 27.2 percent to 2.2 percent from first to third dose Amongst the various reasons for not immunizing the child, the most common in both rural (70.2%) and urban areas (72.7%) was unawareness for the need of vaccination, however in rural areas lack of availability of services (80.2%) was the major cause for not immunizing the child. Thus the present study shows a low coverage of immunization and Vitamin A prophylaxis in both the areas.